Effect of Vitamin E Supplementation on the Growth Performance of Clarias Sp. - arif fitra; Darmawan Setia Budi; Mohammad Hilmi Maulana; Agustono (Airlangga University, 2023)
The high demand for catfish motivates farmers to increase production by stocking at a high density. The stress response caused by stocking density, which has an effect on fish growth and survival, is one of the challenges associated with catfish farming with high stocking levels. This issue can be resolved by supplementing catfish feed with vitamin E to stimulate growth. This study aims to determine the effect of vitamin E supplementation on catfish growth, feed efficiency, and survival. This study employs the RAL method with five treatments, including feeding catfish seeds with vitamin E levels of 0 mg/kg feed (P1), 50 mg/kg feed (P2), 100 mg/kg feed (P3), 150 mg/kg feed (P4), and 200 mg/kg feed (P5), with each treatment repeated four times. Adding 100 mg of vitamin E per kg of feed resulted in the highest growth rates (1.66 0.05%/day), a feed conversion ratio of 1.2 0.07, and a feed efficiency of 83.46 3.24% when compared to other treatments and was significantly different (p 0.05). The addition of 100 mg of vitamin E to the feed had no discernible effect on survival compared to other treatments. Keyword: Vitamin E, supplementation, growth, Clarias sp.